PROBLEMATIC OF FARMER RIGHTS IN INTERNATIONAL FOOD TRADE - Immanullah, Moch Najib; Hadi, Hernawan; Latifah, Emmy (Yustisia, 2016)
AbstractThe urgency of this study is to analyze the problem concerning the provision of preventive and repressive protection rights for farmers regarding to the International Food Trade based on Agricultural Law, by using normative legal research,  in order to owns a feasible position and competitiveness to the Indonesian Farmers as the subject of International Food Trade. The results of the study shows that the existing regulation has not being able to provide preventive and repressive protection rights for farmers in International Trade. Indonesian Government takes alternative solution by doing the harmonization of Indonesian Law which regulate the international trade, particularly the agricultural trade.